The Development of Principal Curriculum Leadership Capabilities Model for Secondary Schools in Shanghai, China - Chen, Beibei; Laksana, Sangob (Scholar: Human Sciences, 2017)
The purpose of this study aimed to develop principal curriculum leadership capabilities model for secondary schools in Shanghai. Both qualitative content analysis and quantitative survey were employed by this study. From the findings, the highest curriculum leadership capabilities of principals of current practice and expectations are the same factor, namely, empathizing. Findings from the gap analysis showed that the priorities of improvement of curriculum leadership capabilities for principals listed by the ranking of: (1) knower and expertise, (2) skills in curriculum development process, (3) diagnosis, (4) building a learning school, (5) strategy, (6) influencing, (7) self-regulation, (8) flexibility and responsiveness, and (9) decisiveness. All above major findings and the foundational theories including Shanghai context and academic leadership capabilities framework (Fullan & Scott, 2009) along with its supported theories were utilized to create the model. The proposed model was constructed in form of bloom graphics presenting its vision, mission, objectives, as well as its applications. It will be applied to equip principals well to shape the future curriculum leadership: leading from curriculum to currere in order to meet the needs of students and the society, and also, make principals become change capable curriculum leaders who have been dedicating to school sustainable development orientated to “Go global, and Stay local”.